Properties and characteristics of thermoplastic PBT-LCP blend system and the influence of nanosilica N-200 - Lim, Raymond Xin Zheng. (2012)
In this study, LCP was blended with PBT to form blend system with different proportions and Nanosilica N-200 was then added to another yet same blend system with different proportions as well. The scope of this study focuses on the development and characterization of a blend system consisting of LCP, PBT and Nanosilica N-200. The blends were then moulded and the specimens were used for morphological, mechanical and dynamic tests.